6x-3=7x-2

Simple and best practice solution for 6x-3=7x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=7x-2 equation:


Simplifying
6x + -3 = 7x + -2

Reorder the terms:
-3 + 6x = 7x + -2

Reorder the terms:
-3 + 6x = -2 + 7x

Solving
-3 + 6x = -2 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-3 + 6x + -7x = -2 + 7x + -7x

Combine like terms: 6x + -7x = -1x
-3 + -1x = -2 + 7x + -7x

Combine like terms: 7x + -7x = 0
-3 + -1x = -2 + 0
-3 + -1x = -2

Add '3' to each side of the equation.
-3 + 3 + -1x = -2 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -2 + 3
-1x = -2 + 3

Combine like terms: -2 + 3 = 1
-1x = 1

Divide each side by '-1'.
x = -1

Simplifying
x = -1

See similar equations:

| 5x-60=12 | | 9(x-12)=36 | | 9X-18=6y | | -5-4(8+6b)=39-56 | | 5x-9y-8=0 | | 100x-0.52=300x+0.46 | | 5n-19=72 | | 4w+7=58 | | 6.2=2.2+z | | 4-1/0-5 | | (3x+1)-4=4 | | 8.2=10x+7.7 | | -(x^10/32)^4/5 | | 4.4=z-5.6 | | 16x-3=12x+15 | | x-6=5x-24 | | 0.05(10000)+0.08x=0.068(10000+x) | | 5(w-2)=30 | | 4.25+4c=1.8 | | 40x+20=145 | | -6+2(x+3)=24-x | | 8x=3-6x | | -2x^2-7x=-1.5 | | 4c+26=62 | | 9x-1=9(x-6) | | 4x+8+6=3x+6 | | cot*2*x=-2.1 | | 8/tan70 | | Csquared-4c=0 | | 0=-2x^3+15x^2-24x+20 | | 27=103-2f | | y=-2x^3+15x^2-24x+20 |

Equations solver categories